Rechtsprobleme der Akkreditierung von Studiengängen - Immer, Daniel (Universitätsverlag Göttingen, 2013)
The present dissertation addresses the manifold legal aspects of the administrative and constitutional problems of accreditation in german institutions of higher education. Issues are raised in respect to well-known questions concerning the legal nature of accreditation, as well as to the related encroachment upon fundamental rights. Furthermore, new challenges such as system accreditation and the seldom debated issues concerning the contractual relationships of the involved parties, or the democratic legitimation of the accreditation administration and the legal nature of its decisions are discussed. The study also draws comparisons to similarly structured areas of law - in so doing, further questions of modernisation in higher education, the debate surrounding privatisation and legal aspects of the administrative organisation are commented on.